Analisis Pengaruh Risiko Litigasi dan Perlindungan Investor Terhadap Kualitas Laporan Keuangan (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2012-2014) - Putri Clara Shinta; Nanang Shonhadji (Program Magister Akuntansi Unsyiah, 2017)
The quality of the financial statements is an important basis for decision-making parties concerned with the company. This study aimed to obtain empirical evidence about the relationship between the quality of financial reporting, litigation risk, and investor protection. The study used sample of companies listed on the Indonesia Stock Exchange over the period 2012-2014. Data were obtained by purposive sampling method based on certain criteria. The final samples used in this study were 88 companies. Technical analysis used in this research was analysis of Multiple Linear Regression Analysis. Statistical test results showed that the risk of litigation research significant positive effect on discretionary accruals, whereas investor protection does not affect the quality of financial reporting.KEYWORDS : The quality of financial statements, litigation risk, and investor protection.